Dog demography and ecology with reference to rabies in the Amhara region, Ethiopia - Adnie, L.Y.; Jemberu, Wudu T.; Woreta, A.B.; Berju, A.; Mengistu, A.; Wondie, Z.T.; Molla, W.; Mekonnen, S.A. (Elsevier, 2025)
Knowledge of domestic dog ecology and demography has been recognized as central to the design of an effective rabies control program. The study was conducted to assess owned dogs' ecology and demography and to identify predictors associated with dog ownership and rabies occurrence in the Amhara region, Ethiopia.